Color-related chlorophyll and carotenoid concentrations of Chinese kale can be altered through CRISPR/Cas9 targeted editing of the carotenoid isomerase gene BoaCRTISO - Sun, Bo; Jiang, Min; Zheng, Hao; Jian, Yue; Huang, Wen-Li; Yuan, Qiao; Zheng, Ai-Hong; Chen, Qing; Zhang, Yun-Ting; Lin, Yuan-Xiu; Wang, Yan; Wang, Xiao-Rong; et al. (Horticulture research, 2020)
The carotenoid isomerase gene ( BoaCRTISO ) of Chinese kale was targeted and edited using the CRISPR/Cas9 system in the present study. The results showed a high mutation rate (81.25%), and 13 crtiso mutants were obtained. Only two types of mutations, insertions and replacements, were found. Both the total and individual carotenoid and chlorophyll concentrations of the biallelic and homozygous mutants were reduced, and the total levels declined by 11.89–36.33%. The color of the biallelic and homozygous mutants changed from green to yellow, likely reflecting a reduction in the color-masking effect of chlorophyll on carotenoids. The expression levels of most carotenoid and chlorophyll biosynthesis-related genes, including CRTISO , were notably lower in the mutants than in the WT plants. In addition, the functional differences between members of this gene family were discussed. In summary, these findings indicate that CRISPR/Cas9 is a promising technique for the quality improvement of Chinese kale and other Brassica vegetables.